Computational model to design plastic multi-layer films for food packaging to assure a shelf life at the best cost. (January 2014) - Noriega, María del Pilar; Estrada, Omar; López, Iván
A computational model to design plastic food packaging is proposed. The model minimizes the cost of the multi-layer structure satisfying the specific product requirements, using a heuristic optimization algorithm. The product requirements are defined by the expected shelf life, the storage conditions, the water sorption isotherms of foods and the maximum allowable gain or loss of gases (O2, CO2, N2, etc.) and moisture for the packaged food. In order to assure the food shelf life, these product requirements should be fulfilled to estimate the maximum permeance values of the plastic package. The computational algorithm automatically generates different multi-layer film structures that satisfy the product requirements. This algorithm combines different polymeric materials taking into account the barrier properties and cost of each layer, the compatibility between layers, the maximum number of layers and the minimum and maximum film thickness for each layer. Temperature and relative humidity corrections for the permeance calculations are considered. Permeance calculations of several barrier films are compared with oxygen transmission rate (OTR) and water vapor transmission rate (WVTR) measurements. The optimization model algorithm is evaluated by means of standard numerical routines and numerical benchmarking.